Formação acadêmica em educação física: Perfis profissionais, objetivos e fluxos curriculares - Hunger, Dagmar Aparecida Cynthia França [UNESP]; Rossi, Fernanda [UNESP] (My University, 2010)
In this research, characterized as a qualitative study, we aimed to analyze the Job Profiles, Objectives and Curriculum Flows specified in Pedagogical Projects of the undergraduate Courses of Physical Education of public, state and federal universities, in the São Paulo state. We also analyzed their articulations and adequacy to the Institutional Pedagogical Project and Institutional Development Plan. The latest Resolutions of Physical Education in Higher Education and conceptualizations of the Pedagogical Project of Course are presented. The method of approach is current History. There was a documental research in order to analyze the official documents. A limited offering of public courses when compared to private institutions was verified and also, there was a greater offering of bachelor degree courses (expanded and generalized formation) concerning health, sport and leisure fields. Courses defined specifically for teachers' formation and educational gap between the pedagogical discourses and the curriculum structures were also presented. In conclusion, this research indicates the necessity of a change in the curricular mentality in order to implement the pedagogical discourses of courses.
Professional formation in physical education: Job profiles, objectives and curriculum flows
Keywords: Initial professional formation; Pedagogical project of course; Physical education